Alternatives to the economic rationalisation of renewable energy transitions: The Tsitsikamma Community Renewable Wind Farm Story - Pressend, Michelle (School of African and GenderStuds, Anth and Ling, 2024)
Within the climate mitigation discourse, renewable energy technology is understood as vital to reduce coal energy reliance. This discourse which is deeply anthropocentric in its approach understands 'green' energy transitions largely as reliant on reductionist techno-scientific 'solutions' and green economic growth rationalisation. If energy transitions are not engaged with critically, ongoing injustice and extractive relationships are likely to be perpetuated. The aim of this thesis is to show that alternative renewable energy transitions as responses to global warming need to be informed from a relational perspective. Values that are respectful, regenerative, and reciprocal to nature and each other constitute the concept of relationality. This study focused on the Tsitsikamma Community Wind Farm (TCWF) in the Eastern Cape (South Africa) as a site to explore the implementation of a renewable energy project. The site on which the wind farm is built has a colonial land dispossession narrative and the return of the Tsitsikamma Mfengu community to reclaimed land in 1994. The community was a willing partner in the investment of a wind energy public-private partnership. While the beneficiaries were promised improvements to their well-being, instead, the material well-being of this community remains unchanged and the commercial agricultural land degraded. The inequalities and the social-ecological relations of the past persist. The so-called 'win-win' rhetoric is an illusion in climate mitigation approaches and largely serves capital accumulation at the expense of community well-being and restoration of the soil. This study drew inspiration from Moore's (2003) world-ecology framing - history is part of rather than separate from the web of life - a non-dualist version of world history. In the research, a multisited ethnography was used and included tracing the relationships that recognised land history, memory (patterns of material nature of the land) and the entangled relationships between humans and non-humans. The conceptual framing and methodology illuminated erasures consistently overlooked in the anthropocentric climate discourses. As a consequence of those revelations openings for more relational and decolonial conceptualisation(s) based on the profound interrelatedness of life became evident. Relational energy transitions are needed in response to the climate crisis that consider the regenerative possibilities of nature-human interrelatedness. Through this argument, the study contributes an important insight for the uptake of methodology and analysis which transcends the 'resource' logic.